Quantitative analysis of soil sustainability after applying stabilizing amendments in long-term Cd-contaminated paddy soils. (1st October 2021) - Chen, Yi; Zhang, Zhe; Gao, Cheng; Deng, Wenyang; Chen, Wenqing; Ao, Tianqi
Abstract: Considering the biomagnification in food chains, cadmium (Cd) contamination in paddy fields has become concerning. The remediation of soil cadmium by the addition of amendments is a common agricultural practice. However, it remains ambiguous whether amendment use decreases soil environmental quality (SEQ) and sustainability. In this study, five compound amendments with different pH were utilized in long-term Cd-contaminated paddy soils. The SEQ of all treatments was quantitatively assessed according to a comprehensive evaluation mathematical model (Criteria Importance Through Inter-criteria Correlation (CRITIC)–Technique for Order Preference by Similarity to Ideal Solution (TOPSIS)), and the indicators involved in microbial functional gene (MFG) abundance, soil physicochemical and microbiological properties (CMP) and soil microbial function (N-related enzyme and transformation rate, N-ET) were measured. The results show that the SQE and remediation effect (expressed by the decrease in available Cd (ACd ), %) in our treatments were alkaline > natural > acidic except for D alkaline treatment. The significant contradiction between soil SQE and remediation effect in D treatment attribute to its dose effects, which inhibiting microbial nitrogen assimilation and dissimilation and therefore counteracts the promoting effect of the decrease in ACd . Based on this discussion, three alkaline amendments (A, B and D) with similar effective remediation effect were employed in four other Cd-contaminated soils. Results indicated that both negative effect (D treatment) and promoting effect (A and B treatment) existed in the next 3 years. Graphical abstract: Image 1 Highlights: The new evaluation method effectively reduced the redundancy among indicators. Underestimating the contribution of microbial functional genes to SEQ assessment. A significant discrepancy was found between remediation effect and SEQ. The impact of amendments on SEQ exists for a long time.